The Role of Constitutional Law in Improving Student's Critical Thinking Ability Through Online Learning - Abdul Rahman (Al-Daulah : Journal of Criminal Law and State Administration Law, 2022)
Lecturers are required to be effective and up to date in maximizing the use of existing learning technology to respond to the demands of very rapid technological developments and the demands of competition in the era of globalization. The application of self-directed and distance learning should be introduced and implemented in universities. Involvement in the application of online learning systems must be able to encourage students to always think critically. In the present context, critical thinking is a must for students. This paper discusses the role of constitutional law courses in increasing the critical power of students in online learning. This research uses a field study and literature study approach, which combines data obtained from various literature in the form of books, journal articles, and facts in the field. In short, this study found that online learning can be a good support for students to improve their critical thinking skills. However, there are several problems in its implementation which include socio-cultural problems, previous offline learning habits, and the habit of using the latest technology in learning. Well-designed online discussions, critical thinking learning content, and instructions that are formulated and given appropriately are some of the factors needed and become recommendations for lecturers in carrying out online learning to improve students’ critical thinking skills. Keywords: Students’ Critical Thinking, Constitutional Law, Online Learning